XV-XVII. mendeetako Euskal Herriko edizioa ikertzeko materialak - Lopez De Luzuriaga Martinez, Iñaki (EGAN, 2024)
This article sets out to contribute to the understanding of the editing con- text, printers and works existing over the territory of the Basque Country since the late 15th century until the late 17th century. It aims to synthesize, add to and update news and research materials produced on the subject to date. The reader will learn that four decades into its invention by Johannes Gutenberg, the press arrived in the Basque Country, developing gradually first throughout Upper Na- varre on the heat of the Counter-Reformation. As production gained momentum in the late 17th century, printers, initially itinerant and foreigners, settled per- manently in Iruñea (Pamplona), Bayonne, Donostia and Bilbao under the wing of town and regional authorities, while in Araba (Alava), no press was installed until 1722.